Pelaksanaan Keselamatan Pasien Melalui Lima Momen Cuci Tangan Sebagai Perlindungan Hak Pasien - Maria Ariani Wijaya; A Widanti S; Hartanto Hartanto (Soepra: Jurnal Hukum Kesehatan, 2018)
Healthcare-Associated Infections (HAIs) is one of the risks that threaten patient safety. HAIs causing harms to the patient's family and the hospital. Five Moments Hand Hygiene is one of the safeguards to against the risk of infection transmission. However, the compliance of hand washing in Indonesia is not maximal yet.